Tahap Profesionalisme Pegawai Skim Perkhidmatan Penguasa Kastam : Satu Kajian Di Jabatan Kastam Diraja Selangor - Rosli, Mohamad (2002)

(untitled)
This study is to identify the level of professionalism among the officer in service scheme of Superintendent of Customs in Royal Customs Department of Selangor. This study emphasis on five criteria pertaining to the understanding of the profession, acquisition in knowledge and skill, practicing of work ethics, communication skills and the leadership ability. The study on the sample of 86 officer from the populations of 176 officers in the scheme which categorized in four divisions under the state director of Customs namely as Customs Division, Internal Tax, Technical Service Division and Preventive Division. The information and data which been collected from respondent and department of record has been processed using the SPSS software to obtain the frequencies, mean and correlation's between variables. The results of the statistical analysis by using one way ANOVA, Tukey HSD, t- test and Correletion Pearson succesfully determined all the hypothesis which has been developed earlier. The results has been concluded that the level of professionalism of the respondent positively high. The perceptions of the five criteria of professionalism been detected from respondent shown that all the criteria is positively high but the criteria of acquisition of knowledge and skill positively moderate. The test on training programs to correlate with the level of professionalism in the department, shown that there is a positive correlation. Based on this research outcomes a few recommendations and suggestions related to future were suggested to be more specific and meaningful.